The Marine World : A Natural History of Ocean Life. - Dipper, Frances (Wild Nature Press Ser., 2019)
The Marine World is a book for everyone with an interest in the ocean, from the marine biologist or student wanting expert knowledge of a particular group to the naturalist or diver exploring the seashore and beyond.With colour illustrations, line drawings, more than 1,500 colour photographs, and with clear accessible text, this book encompasses all those organisms that live in, on and around the ocean, bringing together in a single text everything from the minuscule to the immense. It includes sections on all but the most obscure marine groups, covering invertebrate phyla from sponges to sea squirts, as well as plants, fungi, bacteria, fish, reptiles, mammals and birds. It incorporates information on identification, distribution, structure, biology, ecology, classification and conservation of each group, addressing the questions of 'what?', 'where?' and 'how?'.Today global warming, overfishing, ocean acidification and pollution are just a few of the ever increasing number of threats and challenges faced by ocean life. Without knowledge of the animals, plants and other organisms that live in the marine world, we cannot hope to support or implement successful conservation and management measures, nor truly appreciate the incredible wealth and variety of marine life.The Marine World is the product of a lifetime spent by Frances Dipper happily observing and studying marine organisms the world over. It has been brought to colourful life by a myriad of enthusiastic underwater photographers and by Marc Dando, the renowned natural history illustrator.